The EIP-AGRI thematic networks: fostering innovation in Europe - Mosquera-Losada, María Rosa; Arias-Martínez, Darío; Taboada-Iglesias, María Jesús; Rodríguez-Rigueiro, Francisco Javier; Santiago-Freijanes, José Javier; Couso-Viana, Ana; Burssens, Sylvia; Feo, Elena; Spanoghe, Pieter; Rigueiro-Rodríguez, Antonio; Fernández-Lorenzo, Juan Luis; González-Hernández, María Pilar; et al. (Frontiers in Agronomy, 2025)
European Horizon 2020-funded thematic networks (TNs) gather existing knowledge and best practices on agriculture and forestry to make them available in easy and understandable formats for end-users, including advisors, farmers, and foresters. The analysis of 28 Horizon 2020 TNs in this study aims at understanding, among others, how innovation deployment is associated with the main EU land uses, implementation areas, or farming types and how specific management is tackled by the EU TNs to further propose future topics that are receiving little attention. The analysis was conducted after interviewing and surveying TN coordinators and partners, whose questions were previously validated. The results of the questionnaires and interviews indicate that TNs mainly tackle arable lands, including all farming types, and most of them have a focus on rural areas, addressing the bioeconomy topic by linking rural, peri-urban, and urban areas. The analysis of multi-actor approach projects, as TNs, can help to provide insights on how to expand agricultural innovation, identifying areas of study and practices less represented and promoting them in future TNs.